2008
DOI: 10.1016/j.brainres.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Fewer active motors per vesicle may explain slowed vesicle transport in chick motoneurons after three days in vitro

Abstract: Vesicle transport in cultured chick motoneurons was studied over a period of 3 days using motion enhanced differential interference contrast (MEDIC) microscopy, an improved version of videoenhanced DIC. After 3 days in vitro (DIV), the average vesicle velocity was about 30% less than after 1 DIV. In observations at 1, 2 and 3 DIV, larger vesicles moved more slowly than small vesicles, and retrograde vesicles were larger than anterograde vesicles. The number of retrograde vesicles increased relative to anterogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…5). In previous studies, histograms of normalized vesicle velocities [37] or unscaled velocities [38,[42][43][44] revealed a similar pattern of peaks. These peaks indicate that the velocities of transported vesicles are constrained to quantized values.…”
Section: Inferring Numbers Of Motors From a Velocity Histogramsupporting
confidence: 58%
See 1 more Smart Citation
“…5). In previous studies, histograms of normalized vesicle velocities [37] or unscaled velocities [38,[42][43][44] revealed a similar pattern of peaks. These peaks indicate that the velocities of transported vesicles are constrained to quantized values.…”
Section: Inferring Numbers Of Motors From a Velocity Histogramsupporting
confidence: 58%
“…These peaks indicate that the velocities of transported vesicles are constrained to quantized values. A likely hypothesis that has been proposed [37,[43][44][45] is that each peak represents a different number of motors actively pulling each vesicle through a viscous medium (as we will discuss below, this hypothesis requires the viscosity of the medium to be greater than about 0.1 Pa•s; a requirement that may not be met in, for example, a squashed-mount Drosophila embryo system [46]). Based on this hypothesis and our measured viscosity of 1.8 Pa•s, we assigned numbers of active motors to each of the constant velocity segments.…”
Section: Inferring Numbers Of Motors From a Velocity Histogrammentioning
confidence: 99%
“…26 Several of these studies reported multimodal profiles even in non-normalized velocity distributions. 5,24,26,29 This suggests that the sizes of tracked vesicles and the effective viscosities they experience were more uniform in these studies than what we measure in our NT2 cell system. Quantized velocities have also been reported in vitro from actin sliding at low myosin densities with the zero-load velocity believed to indicate number of active motors.…”
Section: Velocity Distributionmentioning
confidence: 71%
“…In our previous study of velocities in NT2 cells, we observed a similar multimodal pattern of regularly spaced peaks. 41 Other studies on vesicle velocities have observed quantized velocity distributions in cells such as rat PC12 cells, 14 in chick motor neurons, 5,29 in Drosophila, 24 and in melanosomes of Xenopus melanophores. 26 Several of these studies reported multimodal profiles even in non-normalized velocity distributions.…”
Section: Velocity Distributionmentioning
confidence: 99%
“…There is some precedence for changes in intracellular transport with DIV. For example, one study using the MEDIC technique showed that velocities of organelle transport in chick motor neurons slowed with increasing time in vitro [10]. Figure 2A also shows that even at 3-4 DIV, the pattern of increasing transport with increasing density begins to vaguely emerge as can be seen in the overlapping points seen at 20, 40, and 70 cells per mm 2 .…”
Section: Discussionmentioning
confidence: 92%